"You just took the jump too slowly”: A single case analysis of a mountain bike crash - Lloyd, Mike (Social Interaction. Video-Based Studies of Human Sociality, 2019)
Two online videos are used to analyse social interaction in a mountain bike crash. The first provides context and a contrasting case: we view five mountain bikers taking a large gap jump in quick succession, where it is the fact that they are closely linked that helps establish the minimum speed required to take the jump. Then there is a detailed analysis of a frequently viewed YouTube video showing another group of five riders with a very different experience of a much smaller gap jump. In this case, only two riders are closely linked and we see a different kind of social effect: a watching group encourages one of the riders to take the gap jump solo, when he does not seem to have the necessary skill. As a result, when he attempts the jump, he is knocked unconscious. The analysis shows how coordinated activity does not always benefit participants, which highlights the need to carefully investigate the subtleties of co-operative action.